2014
DOI: 10.3892/ol.2014.1838
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA methylation patterns associated with the gastric cancer genome

Abstract: The objective of the current study was to investigate the characteristics of DNA methylation patterns associated with the gastric cancer genome and to identify clinically useful diagnostic markers and therapeutic targets for gastric cancer. The Infinium 450K methylation microarray was used to compare differential DNA methylation sites of gastric cancer tissue with that of normal gastric tissue. The results of the DNA microarray analysis were confirmed by pyrosequencing. Functional analysis of the differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…DNA methylation (DNAm) is an important epigenetic event that can influence pretranscriptional gene silencing, genetic imprinting, X-chromosome inactivation (XCI), genome stability, and cell fate determination [9]. De novo methyltransferases, namely, DNMT3A and DNMT3B [10,11], play a vital role in tumorigenesis mainly by methylating CpG dinucleotides [12]. Aberrant DNAm in the promoter regions is generally believed to be a hallmark of tumors, which often leads to the transcriptional silencing of tumor suppressor genes (TSGs) and the abnormal activation of oncogenes in tumor cells [13].…”
Section: Ivyspringmentioning
confidence: 99%
“…DNA methylation (DNAm) is an important epigenetic event that can influence pretranscriptional gene silencing, genetic imprinting, X-chromosome inactivation (XCI), genome stability, and cell fate determination [9]. De novo methyltransferases, namely, DNMT3A and DNMT3B [10,11], play a vital role in tumorigenesis mainly by methylating CpG dinucleotides [12]. Aberrant DNAm in the promoter regions is generally believed to be a hallmark of tumors, which often leads to the transcriptional silencing of tumor suppressor genes (TSGs) and the abnormal activation of oncogenes in tumor cells [13].…”
Section: Ivyspringmentioning
confidence: 99%
“…H. pylori and the inflammatory process it triggers may promote GC development by inducing deregulation of the DNA methylome . A number of studies have conducted DNA methylation analysis in GC tumours and their adjacent tissues using candidate gene or genome‐wide approaches; however, these studies were limited to cancer tissue, and the effects of H. pylori were not considered. Three studies have identified methylation signatures in normal gastric mucosa in response to H. pylori infection, but these involved only several genes or partial DNA methylome coverage or did not include GC patients .…”
Section: Introductionmentioning
confidence: 99%
“…Although studies of gastric carcinomas ( 27 , 28 ) employing the single-CpG resolution Infinium array ( 29 ) have recently been published, they did not focus on DNA methylation in the non-cancerous mucosa. In this study, in order to clarify the significance of DNA methylation alterations at the precancerous stage of gastric carcinogenesis, we subjected 109 samples of non-cancerous mucosa (N) obtained from 109 patients with primary gastric carcinomas, and 105 samples of the corresponding tumorous tissues (T), to the Infinium assay.…”
Section: Introductionmentioning
confidence: 99%